Government of Grenada, Annual Statistical Digest, 2022 - Statistical Division, Planning & Development Unit, Ministry of Education, Youth, Sports and Culture (Statistical Division, Planning & Development Unit, Ministry of Education, Youth, Sports and Culture, 2022)
The edition for 2022 is current as of October 2021, with updated statistics for the academic year 2021/22. It contains information on students, teachers and educational institutions. It also contains statistics on Library Services, demand for and supply of resources, school age population and population projections.
Keywords: statistical digest; education statistics